2015
DOI: 10.1186/s40199-015-0119-4
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroandrographolide enhances innate immunity of intestinal tract through up-regulation the expression of hBD-2

Abstract: BackgroundDehydroandrographolide (DA) is one of major active components in the well-known oriental herbal medicine Andrographis paniculata (Burm.f) Nees which belongs to the Acanthaceae family. DA is used for the treatment of infections in China. However, DA has not been found to significantly inhibit bacterial and viral growth directly. The current study investigates the effect of DA on the expression of human β –defensin-2 (hBD-2) in human intestinal epithelial cells and the possible signaling pathways.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…TLR2 signaling induces the activation of multiple downstream pathways such as MAPK and NF-κB (Karikó et al, 2004), both of which are known to increase hBD2 expression (Ogushi et al, 2001; Vora et al, 2004; Wehkamp et al, 2004; Li et al, 2008; Xiong et al, 2015). Our results show that hBD2 level was suppressed by pretreatment with the JNK inhibitor SP600125 in LH2171 SLP-treated cells; in addition, treatment with LH2171 SLP activated JNK signaling in Caco-2 cells whereas TLR2 blockade reduced JNK signaling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TLR2 signaling induces the activation of multiple downstream pathways such as MAPK and NF-κB (Karikó et al, 2004), both of which are known to increase hBD2 expression (Ogushi et al, 2001; Vora et al, 2004; Wehkamp et al, 2004; Li et al, 2008; Xiong et al, 2015). Our results show that hBD2 level was suppressed by pretreatment with the JNK inhibitor SP600125 in LH2171 SLP-treated cells; in addition, treatment with LH2171 SLP activated JNK signaling in Caco-2 cells whereas TLR2 blockade reduced JNK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular components of LAB are recognized by pattern recognition receptors such as TLR expressed by host cells, which activate intracellular signaling pathways (Shida et al, 2009; Kawashima et al, 2013; Kim et al, 2015; Kobatake et al, 2017). Many studies have investigated the regulation of hBD2 expression with variable findings (Ogushi et al, 2001; Vora et al, 2004; Wehkamp et al, 2004; Li et al, 2008; Xiong et al, 2015), underscoring the difficulty in establishing the beneficial effects and mechanisms of action of LAB. Our observation that Lactobacillus SLP induces a host defense response could contribute to the elucidation of LAB functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we have preliminarily described the anti-inflammatory effect of Deh and its effect on intestinal flora in vivo , the mechanism of its anti-inflammatory effect in vivo is still unclear. Wenbi Xiong et al found that Deh upregulates hBD-2 to enhance the innate immunity of the intestine [ 20 ]. Our study found that Deh significantly activated the AMPK signaling pathway and promoted the phosphorylation of AMPK.…”
Section: Discussionmentioning
confidence: 99%
“…Human β-defensin-2 (HBD2) is an inducible antimicrobial peptide [ 19 ]. In addition, it exhibits cytolytic activity against a range of tumor cells that is thought either to destabilize the cellular membrane or to cause the formation of open pores which allow vital biomolecules leaking out of the cell.…”
Section: Introductionmentioning
confidence: 99%